The Detection of Earnings Management of the Companies in the Industrial Sector of the Republic of Serbia - Bešlić, Ivana; Bešlić, Dragana; Jakšić, Dejan; Andrić, Mirko (Industrija, 2015)
This paper analyzes the predictive power of existing foreign models for the detection of earnings management of the companies and based on a representative sample of companies in the industrial sector of the Republic of Serbia in attempts to develop an improved model for the detection of manipulative financial reporting which will be suitable for the Serbian business environment by using multiple linear regression. The application of existing foreign models of discretionary accruals in the Serbian economic environment shows that these predictive models do not have sufficient explanatory power (Jones model 5.4%; Dechow model 2.6%; Kasznik model 37%), and there is a need for their further modifications. From these models, only Kasznik model proved to be statistically significant model for the sample of 65 companies in the industrial sector of the Republic of Serbia. As a result of the research, a modified model of discretionary accruals has been developed, which has improved explanatory power and which allows detection of new techniques of manipulation of financial reporting in the industrial sector of the Republic of Serbia. The explanatory power of our modified model is 63.7%.
Keywords: Serbia; Modified model of discretionary accruals; Industrial sector; Earnings management